Hyperstability of the Fréchet Equation and a Characterization of Inner Product Spaces - Anna Bahyrycz; Janusz Brzdęk; Magdalena Piszczek; Justyna Sikorska (Journal of Function Spaces and Applications)
We prove some stability and hyperstability results for the well-known Fréchet equation stemming from one of the characterizations of the inner product spaces. As the main tool, we use a fixed point theorem for the function spaces. We finish the paper with some new inequalities characterizing the inner product spaces.